PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS’ PERCEPTION OF WORKS OF ART - Kasimova Kamila Makhammadzhonovna (Western European Studies, 2024)
this article shows the peculiarity of the perception of works of art by students. The perception of a literary work of fiction is considered "a complex mental and psychological process, a special type of activity that includes various areas of the psyche."
Keywords: Emotional-figurative; intellectual-evaluative; moral personality